Physicochemical and Microbiological Changes Associated with Processing in Dry-Cured Tuna - Mónica Sánchez-Parra; José L. Ordóñez-Díaz; Jesús Pérez-Aparicio; José M. Moreno-Rojas (Applied Sciences, 2023)
Dry-cured tuna is a traditional product manufactured in the Mediterranean region of Spain, known as mojama. The traditional salting-drying elaboration process attributes new organoleptic characteristics to the final product, changing its flavor, color, and nutritional value. This study aimed to evaluate the changes in physicochemical, biochemical, and microbiological parameters taking place during the process. The physicochemical parameters were affected by the processing steps (salting, salt-washing, and drying), except for total acidity and pH. The water activity value and relative moisture percentage decreased to 0.86 and 33.03%, respectively. Moreover, the addition of salt and the drying step increased the water-holding capacity. The lipid oxidation values increased from raw tuna loins to the final product (1.37 vs. 5.56 mg malondialdehyde/kg). Moreover, the total volatile basic nitrogen values increased in the final product, fundamentally due to the concentration effect caused by the water loss, although may also be due to the degradation of proteins during processing. The microbiological analysis showed that the values obtained in the dry-cured tuna were below the limits established by the reference regulation for dry-cured fish products.